2014
DOI: 10.1073/pnas.1420105111
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer photoregulation in vivo

Abstract: The in vivo application of aptamers as therapeutics could be improved by enhancing target-specific accumulation while minimizing off-target uptake. We designed a light-triggered system that permits spatiotemporal regulation of aptamer activity in vitro and in vivo. Cell binding by the aptamer was prevented by hybridizing the aptamer to a photo-labile complementary oligonucleotide. Upon irradiation at the tumor site, the aptamer was liberated, leading to prolonged intratumoral retention. The relative distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 55 publications
4
55
0
Order By: Relevance
“…It was shown that the adsorption of aromatic molecules on silver is often accompanied by the metal-adsorbate charge transfer that is strongly affected by the surface potential. [77][78][79] The above results for neocuproine suggest that the freer rotation of the methyl groups at more negative electrode potential takes place due to the charge transfer process. Apparently when the electrode potential is shifted to more negative values, the charge transfer is activated, and in the vicinity of the zero charge potential (ca.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the adsorption of aromatic molecules on silver is often accompanied by the metal-adsorbate charge transfer that is strongly affected by the surface potential. [77][78][79] The above results for neocuproine suggest that the freer rotation of the methyl groups at more negative electrode potential takes place due to the charge transfer process. Apparently when the electrode potential is shifted to more negative values, the charge transfer is activated, and in the vicinity of the zero charge potential (ca.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the answer that whether endocytosis increase in ovarian cancer compared to normal should be revealed? If the answer is yes, chemotherapy or radiotherapy agents, famous for their side effects, can be coupled to aptamers [34].…”
Section: Discussionmentioning
confidence: 99%
“…This experiment thus permits the examination of the overlap of 3HP SDA-generated green fluorescence and DT1-generated red fluorescence inside cells.DT1 has two sequence elements, one for binding AS1411 (to achieve cancer cell targeting) and the other for binding HPa (to initiate 3HP SDA). AS1411 is aD NA aptamer with high affinity for nucleolin known to express on the surface of various cancer cells, [18] and has been successfully used in previous studies for both cancer cell targeting [19] and selective internalization to the surface of nuclei. [20] In this experiment, AS1411 was modified to contain asequence tag that binds DT1.…”
Section: Angewandte Chemiementioning
confidence: 99%